Anaesthesia-induced atelectasis in a rat model (Rattus norvegicus) - Piskovská, A.; Kraszewska, K.; Gajewski, M.; Skoric, M.; Jekl, V. (Frontiers in Veterinary Science, 2026)
IntroductionAnaesthesia-induced atelectasis has been observed in many animal species, developing during intravenous or inhalational anaesthesia, with or without mechanical ventilation. Ultrasonography of the lungs is a rapid and non-invasive method that has been shown to be effective in detecting atelectasis. This article aimed to describe anaesthesia-induced atelectasis diagnosed through lung ultrasound in a rat model under isoflurane anaesthesia.MethodsA total of 12 clinically healthy, 6-month-old rats (Rattus norvegicus, Wistar rat; body weight 509.4 ± 109.6 g; mean ±SOD) were used in this study. Lung ultrasound was performed at three time points: (i) 5 min before anaesthesia; (ii) during induction of anaesthesia, when the animal was already wearing the facial mask—immediately after the loss of the righting reflex; and (iii) 2 min after the loss of the righting reflex. Moreover, 5-s video loops were recorded at each time point. At the end of the experiment, the animals were euthanised and subjected to histopathological examination. A modified version of the Oricco’s lung ultrasound score (LUSS) was adapted for use in rats. The video loops were anonymised by the operator and re-scored by two independent scorers to obtain the interobserver agreement score.ResultsThe LUSS of all conscious animals showed no pathological changes in the lungs. The adapted LUSS proved to be easy to understand and was consistently applied by all observers. The analysis showed a moderate level of agreement between experts in the assessment of recordings obtained before anaesthesia (0.40 < Kendall’s tau < 0.59) and a very high level of agreement in the assessment of recordings obtained during the induction of anaesthesia and 2 min after the onset of anaesthesia. Additionally, there was a strong consensus regarding the overall assessment of recordings obtained before, during, and after anaesthesia (0.80 < Kendall’s tau < 1.00). Histopathological examination revealed no abnormal findings in any of the animals.ConclusionIn conclusion, anaesthesia-induced atelectasis can lead to marked ultrasonographic changes in gravity-dependent areas in a rat model anaesthetised with isoflurane. The modified version of Oricco’s LUSS showed significant interobserver agreement, indicating its potential reliability for thoracic ultrasound examinations in laboratory and pet rats.